Ocular blood flow measurements in healthy white subjects using laser speckle flowgraphy - Luft, Nikolaus (2018)
Purpose: To assess the feasibility and reliability of Laser Speckle Flowgraphy (LSFG) to measure ocular perfusion in a sample of healthy white subjects and to elucidate the age-dependence of the parameters obtained. Methods: This cross-sectional study included 80 eyes of 80 healthy, non-smoking white subjects of Western European descent between 19 and 79 years of age. A commercial LSFG instrument was applied to measure ocular blood flow at the optic nerve head (ONH) three successive times before and after pharmacological pupil dilation. The mean blur rate (MBR), a measure of relative blood flow velocity, was obtained for different regions of the ONH. Eight parameters of ocular perfusion derived from the pulse-waveform analysis of MBR including blowout time (BOT) and falling rate (FR) were also recorded. Results: Artifact-free LSFG images meeting the quality criteria for automated image analysis were obtainable in 93.8% without pupil dilation and in 98.8% with pharmacological pupil dilation. Measurements of MBR showed excellent repeatability with intraclass correlation coefficients ≥ 0.937 and were barely affected by pupil dilation. The majority of pulse-waveform derived variables exhibited equally high repeatability. MBR-related blood flow indices exhibited significant age dependence (p<0.001). FR (r = 0.747, p<0.001) and BOT (r = -0.714, p<0.001) most strongly correlated with age. Conclusions: LSFG represents a reliable method for the quantitative assessment of ocular blood flow in white subjects. Our data affirms that the LSFG-derived variables FR and BOT may be useful biomarkers for age-related changes in ocular perfusion.